Sports in natural environment, sports in urban environment: An fmri study about stress and attention/awareness - Baena-Extremera, Antonio; Fuentesal García, Julio; Catena Martínez, Andrés; Martín-Pérez, Cristina (Journal of Sport Science and Medicine, 2022)
This study aimed to explore, on one side, the differences between a group of athletes exercising outdoor (OG) and another group exercising indoor (IG) in stress and awareness, and, on the other side, between-group differences in the fMRI activations during the visualization of natural environment images versus urban im-ages. In addition, we aimed to analyze the associations between the resulting task-related brain activations and stress and atten-tion-awareness in each group separately. All the participants (N = 49; OG = 21, 11 females, mean age = 40, SD = 6.49; and IG = 25, 11 females, mean age = 40; 6.19) underwent an fMRI scan and completed the Perceived Stress Scale and the Mindful Attention Awareness Scale. Besides, we collected a sample of hair cor-tisol. Participants viewed three types of images: water nature, green nature and urban images. Two-sample t-test with corrected p=0.001 values were carried out. Further correlational analyses were performed to estimate the associations between task-related brain activations and our pyscho-emotional measures in each group. Fisher tests were used to explore for potential between-group differences in the correlational indexes. In OG, compared to IG, we found a higher activation of the middle occipital cortex and a cluster comprising the supplementary motor area (SMA), the premotor cortex and the pre-SMA while viewing green nature images versus urban images. In OG, more than in IG, the higher activation of the left SMA cluster negatively correlated with perceived stress, while in the IG, more than in OG, the higher pre-motor cortex activation was positively related to the total score on MAAS. No significant association was found with the hair cor-tisol levels. Exercising outdoor would relate to better psycho-emotional outcomes, also for athletes. On the other side, the ex-position to green nature led to higher activation of brain areas related to motor planning, but also to emotion regulation and emotional response.
Keywords: attention/awareness; FMRI; hair cortisol; outdoor exercise; stress; Scopus; JCR